2018
DOI: 10.1590/1676-0611-bn-2017-0507
|View full text |Cite
|
Sign up to set email alerts
|

Simple does not mean poor: grasslands and forests harbor similar ant species richness and distinct composition in highlands of southern Brazil

Abstract: Several studies addressed ant communities in the dense Atlantic Forest that runs along the Brazilian coast. However, comparatively little is known about the mixed forests and grasslands that occur in the southern range of the Atlantic Forest domain. In this study we performed the first standardized assessment of ants in the forest-grassland mosaic found in the highlands of the state of Santa Catarina. We aimed to investigate and compare ant richness and composition between mixed forests and grasslands in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…At a local scale, our study did not show differences in ant diversity between adjacent grasslands and forests, corroborating both Pinheiro et al [31] and Klunk et al [32] for South Brazil, even when more than one stratum (ground, leaf litter and arboreal) is considered (as discussed by Klunk et al [32]). Overall, studies have showed open ecosystems such as grasslands/savannas harboring higher ant diversity than forests in ecotones or landscape mosaics, for many regions of the world (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At a local scale, our study did not show differences in ant diversity between adjacent grasslands and forests, corroborating both Pinheiro et al [31] and Klunk et al [32] for South Brazil, even when more than one stratum (ground, leaf litter and arboreal) is considered (as discussed by Klunk et al [32]). Overall, studies have showed open ecosystems such as grasslands/savannas harboring higher ant diversity than forests in ecotones or landscape mosaics, for many regions of the world (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Locally, we expect compartmented ant assemblages inhabiting forests and grasslands, but no detection of differences regarding species diversity between habitats, as reported similarly by Pinheiro et al [31] and Klunk et al [32] for the same region. As ants are thermophilic organisms, local temperature should positively influence the diversity of ant species found foraging [33].…”
Section: Introductionsupporting
confidence: 70%
“…Our systematic review of ant biodiversity surveys in different biomes over the last five years revealed a bias towards Tropical & Subtropical Grasslands, Savannahs & Shrublands (eight studies, Cross et al 2016 , Van Schalkwyk et al 2019 , Arcoverde et al 2016 , Lasmar et al 2020 , Dröse et al 2019 , Hlongwane et al 2019 , de Queiroz et al 2020 , Santoandré et al 2019 ). We found two studies on Tropical & Subtropical Moist Broadleaf Forests ( Lawes et al 2017 , Klunk et al 2018 ), one study on Tropical & Subtropical Coniferous Forests ( Cuautle et al 2016 ), three studies on Temperate Broadleaf & Mixed Forests ( Braschler and Baur 2016 , Helms et al 2020 , Heuss et al 2019 ), one study on Montaine Grasslands & Shrublands ( Jamison et al 2016 ), three studies on Mediterranean Forests, Woodlands & Scrub ( Adams et al 2018 , Catarinue et al 2018 , Flores et al 2018 ) and one study on Deserts & Xeric Shrublands ( Álvarez and Ojeda 2019 ). In the last five years, only two citations have included information on ants in Temperate Grasslands, Savannahs and Grassland biomes ( Ramos et al 2018 , Kim et al 2018 ), the biome that encompasses Palouse Prairie (Fig.…”
Section: Resultsmentioning
confidence: 99%